The Growth of Lygodium circinnatum (Burn.F.) Swartz) Plants with Fertilization and Different Types of Vines Poles in the Research Forest Area of Rarung, Central Lombok - Wayan Widhana Susila; Ryke Nandini; Ali Setyayudi (Jurnal Perbenihan Tanaman Hutan, 2021)
Ketak (Lygodium circinnatum (Burm.F) Sw.) is one of the main species of non-timber forest products (NTFPs) in West Nusa Tenggara. Ketak produce tendrils that was used as a raw material for the woven handicraft industry. The sustainability of the handicraft  business  has constraints in decreasing the supply of raw materials because the potential is very reduced in nature so that it is necessary to make efforts to cultivate L. circinnatum plants. The aim of the study was to determine the success of planting L. circinnatum with fertilization and different types of vines. The research used a randomized block design which was arranged factorially with a combination of different types of fertilizers (goat manure, cow manure, NPK fertilizer) and vine trees (Gliricidia sepium, Erythrina variegata, bamboo). For six months, the application of fertilizers and different types of climbing stems significantly affected the increase in tendril length and number of leaves and there was an interaction between the two treatments tested;  while the increase in the number of tendrils and life percentage occurred the effect of a single treatment. Goat fertilizer and climbing species G. sepium were the best treatments for the increase in tendril length (73.4 cm) and number of leaves (88 sheet). The best NPK fertilizer treatment for the growth of the number of tendrils (3 tendrils), climbing species G. sepium and goat manure produced the highest percentage of life (80.42% and 85.56%)